Investigation of shape memory polymers for dental applications - Chen, Ming Yuan. (2012)
This research describes an investigation of shape memory polymers for dental applications. To study the mechanism of shape memory polymer effect of shape memory polymer which can be reactivated to apply a new force vector onto specific teeth and relationship on how will it be implemented to straightening of teeth from traditional wire approach to the Invisalign plastic trays. The thermoplastic polymer is explained by obtaining the glass transition temperature and training temperature after Differential Scanning Calorimeter (DSC) test. The cyclic loading and unloading stress-strain relationships obtaining from the experiments determine the different strains shape fixity, Young’s modulus and so on. In additional, the extension experimental data are demonstrated and analyzed to understand the optimum shape recovery rate, as well as the characterization of shape memory polymer under different conditions of loading forces and heating rates. X-ray diffraction test is also carried out to examine the degree of crystallinity in polymer. Through the varied methods to quantify all the characteristics of each experiment leading to approve that shape memory polymer is a new, novel, user centric approach for a bio-compatible as future trend for dental application.